Our experience in the use of revascularized flaps in the surgical treatment of patients with soft tissue sarcomas - V. V. Ivanov; O. I. Kaganov; A. E. Orlov; A. N. Nikolaenko; S. O. Doroganov; I. V. Bondarenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Soft tissue sarcomas (STS) are quite rare malignant tumors of mesenchymal origin. The incidence is up to 2% among all malignant neoplasms. In Russia, about 10,000 new cases of STS are registered annually. For a long time, the main treatment method for patients with soft tissue sarcomas of the extremities was amputation, which led to a decrease in quality of life and disability. Currently, thanks to a multidisciplinary approach, it has been possible to develop optimal tactics in the complex treatment of patients with this pathology. The modern view on the treatment of this group of patients involves drug therapy and adequate excision of the tumor, observing the ablastic principles. A necessary condition is that the distance from the palpable edge of the tumor should be 5-8 cm. Due to this indentation, the question arises of closing extensive post-resection soft tissue defects. This aspect creates certain difficulties in the treatment of patients with tumor localization, mainly in the distal parts, such as the hand and especially the foot. The purpose of this work is to analyze the experience of using revascularized flaps in the surgical treatment of patients with soft tissue sarcomas. The study was conducted at the Center of Oncology-Orthopedics of the Samara Regional Clinical Oncology Center.Object and methods. From 2020 to 2023, our observation included a group of patients of 10 people, 6 women and 4 men, ages from 29 to 64 years. Nosological types were: spindle cell sarcoma, liposarcoma, fibrosarcoma (pT1.2a-bN0M0, GI-III, IAB, IIA-B, stage III). All patients underwent surgical interventions, which included radical removal of the soft tissue tumor and the reconstructive stage of replacing the post-resection defect using revascularized flaps on microvascular anastomoses.Results. The main advantage of the reconstructive stage using microsurgical technology is the rapid restoration of the skin, replenishment of soft tissue deficits, including thickness, the strength of the flap to perform the supporting function, the absence of trophic disorders, the absence of joint contracture, restoration of limb function in the shortest possible time. The follow-up period was 3 years. During this time, the following were noted: relapse – 0, thrombosis of the microvascular anastomosis – 0, marginal necrosis of the flap – 1, joint contracture – 0. The relative disadvantages of using this technique include: the duration of the surgical intervention, the need for simultaneous work of several surgical teams, the constant improvement of the surgeon's manual and practical technique, the labor intensity of such operations and the mandatory availability of special optical equipment and suture material.Conclusion. The use of revascularized flaps in the surgical treatment of patients with soft tissue sarcomas makes it possible to radically remove the tumor and fully replace the post-resection defect, which in turn reduces the risk of relapses and promotes restoration of limb function with a good cosmetic result.